The Legal Analysis of Judges’ Considerations in Adjudicating Theft Crimes Committed by Women - Zulkarnain, Zulkarnain Hasibuan; Syahril (Faculty of Law-Universitas Bandar Lampung, 2025)
The law serves to regulate relationships between individuals and between individuals and the state so that everything runs in an orderly manner. In the Criminal Code (KUHPidana), theft is classified into various categories, including, as stipulated in Article 362 of the Criminal Code, theft with aggravating circumstances. Theft with crime is a crime against property. The crime committed in theft has the purpose of preparing or facilitating theft or, if caught, providing an opportunity for the perpetrator to escape so that the stolen goods remain in the perpetrator's possession. The problem is the gap between das sollen and das saen, the difference between what should be and what is in reality. In relation to the topic raised in this study, the problem is: How should criminal punishment be imposed on women who commit theft? How is Article 362 applied to a woman who commits theft? To find out the reasons why a woman commits theft. To find out how Article 362 is applied to a woman who commits theft. The type of research used in this study is normative empirical research using secondary data sources and legislation.